INTERNALISASI KARAKTER RELIGIUS PADA PESERTA DIDIK KELAS RENDAH MELALUI PEMBIASAAN PAGI DI MIS LAA TAHZAN KABUPATEN SERANG - Rianti, Nurfatin Melina; Jamaludin, Ujang; Jamaludin, Damanhuri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The internalization of religious character was a significant process in the realm of education, particularly at the primary school level. This study explored how lower-grade students internalized religious values through their morning practices. The research used a qualitative method, with descriptive approach. This study was carried out at MIS Laa Tahzan from November 2024 to May 2025. The number of informants included the Principal School, Homeroom Teacher of 3rd Grade, Homeroom Teacher of 1st Grade, and low-grade level students of MIS Laa Tahzan, who selected using quota sampling. Data were gathered using interviews, observations, and documentation. The Miles and Huberman interactive analysis model was utilized for analyzing data. Data were examined using the Miles and Huberman interactive analysis methodology. The study's findings revealed that habituation activities at MIS Laa Tahzan included muraja'ah, reciting the Al-Qur’an, learning hadiths, dhikr, congregational Dhuha prayer, and the Al-Qur'an Reading and Writing (BTQ) program, which ran every day from 07.15 WIB to 09.30 WIB. The method of adopting religious character internalization was not only goal-oriented, but it also additionally encourages profound habituation. Students were taught a religious attitude through habituation practices, which includes discipline, honesty, responsibility, devoted worship, and other desirable behaviors. Consequently, the implementation of morning habituation exercises at MIS Laa Tahzan was integrated into the school culture and served as a tangible example of religious character education that was systematic, effective, and pertinent to the development of students' spiritual morals within the framework of basic education